Experimental and Numerical Comparison of Replaceable Sleeve Fuses and Reduced Web Sections for Improved End-Plate Bolted Connection Performance - Atar, Muhammed (Mdpi, 2025)
Steel moment-resisting frames rely on strength and ductility to perform under seismic loads. Conventional techniques such as reduced beam section (RBS) and reduced web section (RWS) improve ductility by relocating plastic hinges but can suffer from local buckling, fabrication challenges, and costly post-earthquake repairs. This study proposes a sacrificial steel sleeve fuse system for bolted endplate connections, designed to concentrate inelastic deformation within a replaceable sleeve while preserving the primary structural components. Experimental tests included standalone sleeve compression, bolted sleeve assemblies, and T-stub connections with and without sleeves, all validated with finite element models. A parametric study evaluated two sleeve geometries-circular wave (CW) and U-shaped (US)-and compared the sleeve fuse system's monotonic performance with RWS and standard connections. Results indicate that properly designed sleeve fuses significantly enhance ductility and energy dissipation without compromising initial stiffness or strength, achieving up to 1.8 times the ductility and 25.9% higher energy absorption relative to RWS connections. The findings highlight the sleeve fuse as an innovative, easily replaceable, and resilient solution for seismic applications, offering a practical path for both retrofitting existing frames and designing new structures.
Keywords: sleeve fuse; RWS; bolted end-plate connections; monotonic loading; energy dissipation; structural ductility